2006
DOI: 10.1088/0026-1394/43/2/s24
|View full text |Cite
|
Sign up to set email alerts
|

Determination of distance offsets of diffusers for accurate radiometric measurements

Abstract: A method for the determination of the effective measurement plane of spectroradiometer diffusers at various wavelength regions is described. The method is based on the inverse-square law of the distance dependence of the measured signal. The scheme is tested with three planar and one dome-shaped spectroradiometer diffuser at four wavelength bands. The distance offsets of the diffusers determined in the UVA region are from 0 mm to 2.1 mm for the planar diffusers and 6.4 mm for the dome diffuser, whereas the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…By adapting calculations performed for similar diffusers [ Bernhard and Seckmeyer , 1997; Hovila et al , 2005], we estimated that the reference plane for irradiance calibrations could be about 2 mm behind the diffuser's top. Recent experimental evidence conflicts with theoretical calculations, indicating that the offset for shaped diffusers may exceed the height of the diffuser [ Manninen et al , 2006; Gröbner and Blumthaler , 2007]. Preliminary tests with the UV9 diffuser have indicated that its reference plane could be as much as 5 mm behind the diffuser's top.…”
Section: Discussionmentioning
confidence: 99%
“…By adapting calculations performed for similar diffusers [ Bernhard and Seckmeyer , 1997; Hovila et al , 2005], we estimated that the reference plane for irradiance calibrations could be about 2 mm behind the diffuser's top. Recent experimental evidence conflicts with theoretical calculations, indicating that the offset for shaped diffusers may exceed the height of the diffuser [ Manninen et al , 2006; Gröbner and Blumthaler , 2007]. Preliminary tests with the UV9 diffuser have indicated that its reference plane could be as much as 5 mm behind the diffuser's top.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have shown that the traditional assumption of determining the reference plane of shaped diffusers by geometrical calculations systematically underestimates the actual reference plane obtained from careful laboratory measurements. 4,5 Indeed, Manninen et al 4 calculated the reference plane of the J1002 diffuser to be 2 mm inside of the dome when measured from the top of the dome by use of a simple geometrical model and showed that this result is in contrast with their laboratory measurements, which locate the reference plane 5.3 mm behind the top of the dome, a difference of more than 3 mm relative to the theoretical calculation.…”
mentioning
confidence: 92%
“…Therefore errors in the distance measurement during the calibration process will introduce nonnegligible systematic errors in solar measurements if the reference plane of the entrance optic is not determined correctly. In the case of the J1002 diffuser, Manninen et al 4 claimed an underestimation of solar irradiance measurements of 2% when the instrument was calibrated at a distance of 500 mm from the reference irradiance source, and the top of the dome was used as the reference plane of the diffuser.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 The nonideal angular responsivity may cause a systematic measurement error if not accounted for. Although broadband UV detectors, as well as the measuring heads of spectroradiometers, are often equipped with diffusers, the angular responsivities of the detectors typically differ somewhat from the ideal cosine shape.…”
Section: Introductionmentioning
confidence: 99%